Health Effects of Consuming Vegetables Grown in the Presence of Salt: A Systematic Review - Sossou, Hermeline Ericie; AGUEH, VICTOIRE DAMIENNE AGOSSI; Awede, Bonaventure; LAGNIKA, LATIFOU; YESSOUFOU, AKADIRI; GANDONOU, Christophe (My University, 2022)
In arid and semi-arid areas, salinity problems are common due to several factors. In Africa, salinity and alkalinity affect 24% of the continent’s arid and semi-arid areas and about 30% of the African population depends on these lands. This salinity is not without consequences for crops. The objective of this systematic review is to update research knowledge on the effects of salt stress on vegetables and consumers. To achieve this, several searches were conducted in four search engines and bibliographic databases of electronic scientific journals (PubMed, African Journal Online, Google scholar and Cochrane). The PICO-based research question for this synthesis was: In rats consuming mutant or non-mutant vegetables grown in the presence of salt, does the consumption of mutant or non-mutant vegetables grown in the presence of salt have an impact on the health of consumers? A total of 321 articles were available in the scientific journals explored, only three addressed the effect on nutritional aspects and none of them addressed the health effects of vegetables grown in the presence of salt. The results of these interventions revealed that salt stress altered the nutritional profile of the plants explored. This alteration was reflected in variations in vitamin and mineral content. Moreover, salt stress could also alter the number of fruits on the plants. This systematic review will therefore contribute to the implementation of research on the impact of the consumption of vegetables grown in the presence of salt on the health of consumers.
Keywords: Consumption; Vegetables; Salt Stress; Health